Abu Nasr al-Farabi and Europe’s discovery of Aristotle - Joseph Ellul, O.P. (Journal of Oriental Studies, 2020)
On September 22, 2001, several days after the terrorist attack on the World Trade Center in New York, Pope (now Saint) John Paul II began a two-day pastoral visit to Kazakhstan. During this event he delivered speeches addressed to various audiences, from the Head of State who at the time was Nursultan Nazarbayev, to young people and university students. Already in the speech delivered on his arrival at Astana Airport, he demonstrated his admiration for the rich intellectual, cultural and religious heritage of the country he would be visiting. Among the great minds who were born in Kazakhstan he mentioned “Abu Nasr al-Farabi, who helped Europe to rediscover Aristotle” (John Paul II, 2001). The purpose of this article is to discuss the Pope’s reference to Aristotle’s influence on al-Farabi’s Ihsa’ al-’Ulum (The Enumeration of the Sciences), the latter’s interpretation of the Stagirite’s classification of the sciences in a Neoplatonic key. After examining Aristotle’s influence on al-Farabi, we will consider how the latter’s work came to influence academic life in mediaeval western Christendom. I will then cite one case among many of al-Farabi’s influence on mediaeval Christian thought, namely the philosophical project of Albert the Great (d. 1280). Key words: al-Farabi, Aristotle, sciences, philosophical system, translation, adoption.